Sensitization to autoimmune hepatitis in group VIA calcium-independent phospholipase A2-null mice led to duodenal villous atrophy with apoptosis, goblet cell hyperplasia and leaked bile acids - Jiao, Li; Gan-Schreier, Hongying; Tuma-Kellner, Sabine; Stremmel, Wolfgang; Chamulitrat, Walee (Biochimica et biophysica acta. Molecular basis of disease, 2015)
Chronic bowel disease can co-exist with severe autoimmune hepatitis (AIH) in an absence of primary sclerosing cholangitis. Genetic background may contribute to this overlap syndrome. We previously have shown that the deficiency of iPLA2β causes an accumulation of hepatocyte apoptosis, and renders susceptibility for acute liver injury. We here tested whether AIH induction in iPLA2β-null mice could result in intestinal injury, and whether bile acid metabolism was altered. Control wild-type (WT) and female iPLA2β-null (iPLA2β−/−) mice were intravenously injected with 10 mg/kg concanavalinA (ConA) or saline for 24 h. ConA treatment of iPLA2β−/− mice caused massive liver injury with increased liver enzymes, fibrosis, and necrosis. While not affecting WT mice, ConA treatment of iPLA2β−/− mice caused severe duodenal villous atrophy concomitant with increased apoptosis, cell proliferation, globlet cell hyperplasia, and endotoxin leakage into portal vein indicating a disruption of intestinal barrier. With the greater extent than in WT mice, ConA treatment of iPLA2β−/− mice increased jejunal expression of innate response cytokines CD14, TNF-α, IL-6, and SOCS3 as well as chemokines CCL2 and the CCL3 receptor CCR5. iPLA2β deficiency in response to ConA-induced AIH caused a significant decrease in hepatic and biliary bile acids, and this was associated with suppression of hepatic Cyp7A1, Ntcp and ABCB11/Bsep and upregulation of intestinal FXR/FGF15 mRNA expression. The suppression of hepatic Ntcp expression together with the loss of intestinal barrier could account for the observed bile acid leakage into peripheral blood. Thus, enteropathy may result from acute AIH in a susceptible host such as iPLA2β deficiency.
Gesehen am 22.02.2017